The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/ccd.10478
|View full text |Cite
|
Sign up to set email alerts
|

Secondary embolization of a Helex occluder implanted into a secundum atrial septal defect

Abstract: We report on a 2-year-old patient with atrial septal defect with a stretched diameter of 11 mm. The defect was closed uneventfully by use of a 25 mm Helex device. There was only trivial residual shunting (1 mm at the cranial margin of the device). After 36 hr, routine postinterventional echocardiography confirmed device embolization into the pulmonary artery. The child was asymptomatic. Transcatheter device retrieval with snares of different sizes, bioptomes, and retrieval forceps failed due to the mismatch of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The device requires placement of a 9F short sheath for deployment, and in the event of an embolization, can be successfully retrieved without upsizing to a larger sheath, although upsizing to an 11F sheath is recommended. To date, all patients in the U.S. clinical trial have had successful percutaneous retrieval, even with the few embolizations that were discovered late after placement 5 …”
Section: Product Designmentioning
confidence: 99%
“…The device requires placement of a 9F short sheath for deployment, and in the event of an embolization, can be successfully retrieved without upsizing to a larger sheath, although upsizing to an 11F sheath is recommended. To date, all patients in the U.S. clinical trial have had successful percutaneous retrieval, even with the few embolizations that were discovered late after placement 5 …”
Section: Product Designmentioning
confidence: 99%
“…Electrocardiography and blood tests, including cardiac enzymes and troponin, confirmed the diagnosis of an acute myocardial infarction of type I variant of Kounis syndrome [3][4][5][6][7][8][9]. This variant includes patients with normal coronary arteries without predisposing factors for coronary artery disease in whose the acute release of inflammatory mediators during the allergic reaction can induce either coronary artery spasm without increase of cardiac enzymes and troponins or coronary artery spasm progressing to acute myocardial infarction with raised cardiac enzymes and troponins.…”
mentioning
confidence: 98%
“…Two embolized devices were retrieved using a catheter technique, and 2 patients underwent surgery. Peuster et al [7] reported a clinically asymptomatic secondary embolization of a 25 mm Helex occluder into the pulmonary artery 30 h after implantation into a centrally located secundum ASD with a stretched diameter of 13 mm in a 2-year-old patient. Transcatheter device retrieval with snares of different sizes, bioptomes, and retrieval forceps failed due to the mismatch of the diameter of the device and the small diameter of the pulmonary artery.…”
mentioning
confidence: 99%
“…There are several reports of embolized devices, including embolization to the ventricles [2], aorta [3], pulmonary artery [4], aortic and tricuspid valves. Device dislodgment and embolization are related to patient and procedural factors, including inappropriate sizing of the device, inadequate rims of an atrial septal defect, and a floppy atrial septum [5].…”
mentioning
confidence: 99%